Kaidah-Kaidah Kebahasaan dan Aplikasinya dalam Menafsirkan Al-Qur’an - Dani, Rahmat; Yusuf, Kadar M.; Alwizar (Al-Jadwa: Jurnal Studi Islam, 2023)
This research aims to find out what rules need to be understood in interpreting the Al-Qur'an. The research method used is literature review. The rules of interpretation are a mufassir's tool in understanding the meaning of the Qur'an. The rules of Tafsir are also closely related to the rules of the Arabic language which are one of the foundations for interpreting the Al-Qur'an. Therefore, mastery of linguistic rules is very necessary in interpreting the Al-Qur'an so that the meaning of the Al-Qur'an verses is not misinterpreted. There are several linguistic rules in interpreting the Qur'an that need to be carefully considered, including: Isim Dhamir, Nakirah and Ma'rifah, repetition of words, questions and answers, number of syartiyah. The linguistic rules in interpreting the Al-Qur'an mentioned above are concise rules that need to be mastered by a mufassir when wishing to interpret the Al-Qur'an.